Measurement of Snow Cutting Forces for Analysis and Design of a Snow Ski - KOBAYASHI, Toshiichi; TADA, Noritaka (Journal of Ski Science, 2005)
The turning motion of an alpine snow ski is made possible by centripetal force and the moment around the center of mass. Both the force and moment are produced by resistance forces from the surface of the snow. The centripetal forces are obtained by placing the ski's longitudinal axis at an angle inclined away from the velocity vector and simultaneously edging the ski into the snow. A experimental device rotates a compact snow specimen and cuts it using a cutting tool by simulating the edge of a ski. In order that it can be cut while rotating with the attack angle set up in the whole cutting tool, the circular-arc type cutting tool was developed and it used for the experimental device. The force sensor attached in the cutting tool measured three components of snow cutting force, i.e. a horizontal component inverse to the cutting direction, a vertical upward component to the snow surface, and a transverse component vertical to the cutting and vertical direction. The transverse component corresponds to the centripetal force which makes ski's turning motions possible. The result of an experiment showed the effects of cutting speed, attack angle, and edging angle on snow cutting forces. The snow cutting force equations were obtained by applying multiple regression analysis to experimental data.